Fiber Lasers. Issue 1 (January 2014) - Becker, Frank; Brettschneider, Corinna; Kallage, Peter; Rath, Wolfram
Abstract Fiber lasers have already firmly established themselves within the industrial production sector and are synonymous with efficiency, precision and cost‐effectiveness in a large number of laser material processing applications. They offer excellent single‐mode or multi‐mode beam qualities, which can be precisely adapted to the processing task and therefore represent a universal tool for industrial production. On the basis of selected application examples, the technology and the manifold application possibilities of the Rofin fiber lasers in the power range from 0.5 to 6 kW are reviewed.